Rapid Probabilistic Inundation Mapping Using Local Thresholds and Sentinel-1 SAR Data on Google Earth Engine - Jiayong Liang; Desheng Liu; Lihan Feng; Kangning Huang (Remote Sensing)
Traditional inundation mapping often relies on deterministic methods that offer only binary outcomes (inundated or not) based on satellite imagery analysis. While widely used, these methods do not convey the level of confidence in inundation classifications to account for ambiguity or uncertainty, limiting their utility in operational decision-making and rapid response contexts. To address these limitations, we propose a rapid probabilistic inundation mapping method that integrates local thresholds derived from Sentinel-1 SAR images and land cover data to estimate surface water probabilities. Tested on different flood events across five continents, this approach proved both efficient and effective, particularly when deployed via the Google Earth Engine (GEE) platform. The performance metrics—Brier Scores (0.05–0.07), Logarithmic Loss (0.1–0.2), Expected Calibration Error (0.03–0.04), and Reliability Diagrams—demonstrated reliable accuracy. VV (vertical transmit and vertical receive) polarization, given appropriate samples, yielded strong results. Additionally, the influence of different land cover types on the performance was also observed. Unlike conventional deterministic methods, this probabilistic framework allows for the estimation of inundation likelihood while accounting for variations in SAR signal characteristics across different land cover types. Moreover, it enables users to refine local thresholds or integrate on-the-ground knowledge, providing enhanced adaptability over traditional methods.